Field Observations During the Second Microwave Water and Energy Balance Experiment (MicroWEX-2): from March 17 through June 3, 2004 - Jasmeet Judge; Joaquin Casanova; Tzu-yun Lin; Kai-Jen Calvin Tien; Mi-young Jang; Orlando Lanni; Larry Miller (EDIS)
The goal of MicroWEX-2 was to understand the land-atmosphere interactions during the growing season of corn, and their effect on observed microwave brightness signatures at 6.7 GHz, matching that of the satellite-based microwave radiometer, AMSR.  This document is Circular 1480, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date November 2005.